2013
DOI: 10.2478/10004-1254-64-2013-2358
|View full text |Cite
|
Sign up to set email alerts
|

Liver Aspartate Transaminase Isoenzymes as Biomarkers of Chronic Exposure to Chromium(VI)

Abstract: Exposure to hexavalent chromium compounds is associated with the risk of lung cancer, dermatitis, gastrointestinal ulcers, and other tissue damages. The aim of this study was to compare liver isoenzyme and total serum activities of aspartate aminotransferase (AST) as cytotoxic biomarkers of acute and chronic cytotoxicity of Cr VI . We investigated the extent of cell damage caused by chromium(VI) in acute (2.5 mg kg -1 ) daily doses administered over fi ve days and chronic (0.25 mg kg -1 and 0.5 mg kg -1 ) dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The results of Aksu’s study equally showed that lower levels of organic trace elements did not negatively affect serum biochemical indices in broilers [ 27 ]. When tissue cells are damaged or necrotic, Alanine aminotransferase (ALT) and Aspartate transaminase (AST) are released and their activity in the serum is elevated [ 28 , 29 ]. It has been reported that 1/3 NRC recommended levels of organic trace elements do not significantly affect serum ALT and AST activities in livestock [ 27 ], which is consistent with the results obtained in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Aksu’s study equally showed that lower levels of organic trace elements did not negatively affect serum biochemical indices in broilers [ 27 ]. When tissue cells are damaged or necrotic, Alanine aminotransferase (ALT) and Aspartate transaminase (AST) are released and their activity in the serum is elevated [ 28 , 29 ]. It has been reported that 1/3 NRC recommended levels of organic trace elements do not significantly affect serum ALT and AST activities in livestock [ 27 ], which is consistent with the results obtained in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…33 In general, the liver is one of the important immunological organs, which can involve in immune function, while ALT and AST activities are mainly measured to assess the severity of hepatic tissues and function injuries. 34 According to the study of Najafi et al, 35 rat serum AST activities increased in longterm exposure to hexavalent chromium, whereas Laschtowitz et al 36 researched serum ALT levels in autoimmune hepatitis and cirrhosis patients showed that a considerable proportion of patients with liver injury emerged normal ALT levels. These findings were consistent with our results and suggested that pregnancy and lactation BDE-209 exposure induced female offspring hepatic injury.…”
Section: Discussionmentioning
confidence: 99%